Peaceful resistance : building a Palestinian University under occupation - Baramki, Gabi (Pluto Press, 2009)
This book tells the remarkable story of Birzeit University, Palestine's oldest university in the Occupied Territories. Founded against the backdrop of occupation, it is open to all students, irrespective of income.